Concepções de alfabetização, leitura e escrita que ancoram o Projeto Trilhas - Ferreira, Luiz Costa (2014)
This work has as its object of study the printed Projeto Trilhas, educational material produced in partnership between the Instituto Natura, the Comunidade Educativa CEDAC and the Ministry of Education. It is a documentary analysis which sought to involve the notions of statement, text, gender and support that allowed substantiate the methodological proposal, guided by the dialog, which was as scope problematize as this set of materials can contribute to the process of teaching and learning of children enrolled in classes for the first year of Elementary School, with a focus on the analysis of the conceptions of literacy, reading and writing, engendered in materials. For this reason, the theoretical framework that has mapped out the reflections based on contributions from the perspective Assuming Bakhtin language and launched anchorages in the concept of literacy proposed critically by Gontijo (2008). The analyzes have been constituted as an arena, that is, a stage of alterity. As soon as they sought to understand the concept and the ideas materialize in activities produced by subject-authors and posed problems as the printed output from the Projeto Trilhas can contribute to the improvement of the teaching and learning of children enrolled in the first year of Elementary School. With the analyzes, it is maintained that the concept that solidifies the constitution of printed this project nears the contributions of Ferreiro and Teberosky (1999), that is, literacy is the process by which children acquire the written code and understands the uses that are data in the cultures of writing. The reading is configured as decoding the linguistic signs and understanding of meanings, and writing as coding